Views of my Fellows Thinking (Counting Thoughts)1. (13th December 2017) - Travis, Charles
Abstract: The role of words (language) in thought expression is to make recognisable what thought is expressed. ('Thought' may be read here equally well as a countable or as a mass term.) The role of a definite description in the expression of a singular thought is to make recognisable with respect to what object the thought is singular. That different definite descriptions may play this role for one object settles nothing as to how such thoughts are to be counted. What does settle this? The present brief is: nothing in the (or Frege's) notion of a thought as such. For good reason. A way of counting thoughts is under two opposing constraints. First, it must serve the needs of proof. Second, it must yield thoughts which are shareable (by indefinitely many different thinkers). Simultaneously satisfying both these demands requires there to be no one way of counting thoughts which is the right one tout court. That is, the notion same thought is an occasion‐sensitive notion (admits of different understandings on different occasions for counting).